Dendrimer-conjugated isotretinoin for controlled transdermal drug delivery - Tianqi Zhao; Mingwei Zhou; Ronghui Wu; Huaxin Wang; Christos C. Zouboulis; Mingji Zhu; Myongsoo Lee (Journal of Nanobiotechnology, 2023)
Abstract Background In the present study, we aimed to develop a novel isotretinoin delivery model for treating skin diseases, revealing its potential advantages in drug delivery and targeted therapy. Using a self-assembly strategy, we grafted a dendrimer, based on a well-defined branched structure for nanomedical devices, with a well-defined nanoarchitecture, yielding spherical, highly homogeneous molecules with multiple surface functionalities. Accordingly, a self-assembled dendrimer-conjugated system was developed to achieve the transdermal delivery of isotretinoin (13cRA-D). Results Herein, 13cRA-D showed remarkable controlled release, characterized by slow release in normal tissues but accelerated release in tissues with low pH, such as sites of inflammation. These release characteristics could abrogate the nonteratogenic side effects of isotretinoin and allow efficient skin permeation. Moreover, 13cRA-D exhibited high therapeutic efficacy in acne models. Based on in vitro and in vivo experimental results, 13cRA-D afforded better skin penetration than isotretinoin and allowed lesion targeting. Additionally, 13cRA-D induced minimal skin irritation. Conclusion Our findings suggest that 13cRA-D is a safe and effective isotretinoin formulation for treating patients with skin disorders. Graphical Abstract